2022
DOI: 10.1371/journal.pone.0276929
|View full text |Cite
|
Sign up to set email alerts
|

Reduced humoral but stable cellular SARS-CoV-2-specific immunity in liver transplant recipients in the first year after COVID-19

Abstract: Mortality due to COVID-19 is not increased in immunosuppressed individuals after liver transplantation (OLT) compared to individuals without immunosuppression. Data on long-term protective immunity against SARS-CoV-2 in immunosuppressed convalescents, is limited. We prospectively measured immune responses against SARS-CoV-2 by quantifying antibodies against 4 different antigens (spike protein 1 and 2, receptor binding domain, nucleocapsid) and T cell responses by IFN-γ ELISPOT against 4 antigens (membrane, nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…With respect to the cellular immune response, most LTR are able to develop T cell responses against the spike, nucleocapsid or membrane protein of SARS-CoV-2 99–101. Notably, the magnitude of T cell responses was comparable in LTR and healthy individuals and the cellular immune responses in LTR were longitudinally detectable and remained stable over 12-month postinfection99 100 (figure 2B).…”
Section: Sars-cov-2 and The Adaptive Immune Responsementioning
confidence: 95%
See 1 more Smart Citation
“…With respect to the cellular immune response, most LTR are able to develop T cell responses against the spike, nucleocapsid or membrane protein of SARS-CoV-2 99–101. Notably, the magnitude of T cell responses was comparable in LTR and healthy individuals and the cellular immune responses in LTR were longitudinally detectable and remained stable over 12-month postinfection99 100 (figure 2B).…”
Section: Sars-cov-2 and The Adaptive Immune Responsementioning
confidence: 95%
“…With respect to the cellular immune response, most LTR are able to develop T cell responses against the spike, nucleocapsid or membrane protein of SARS-CoV-2 99–101. Notably, the magnitude of T cell responses was comparable in LTR and healthy individuals and the cellular immune responses in LTR were longitudinally detectable and remained stable over 12-month postinfection99 100 (figure 2B). In a recent study, Citores et al performed a functional analysis of virus-specific CD4+ and CD8+ T cells 12 months after COVID-19 and observed a non-significant trend towards lower levels of IL2, IL10, TNF-α and IFN-γ in LTR compared with healthy individuals 101.…”
Section: Sars-cov-2 and The Adaptive Immune Responsementioning
confidence: 95%
“…Previously, Kirchner et al reported a stable cellular immune response over 1 year in convalescent LTR despite a decline in the humoral response. 27 The clinical significance of a low cellular SARS-CoV-2 immune response in these patients and ways to overcome this require further investigation. However, there is a general understanding that the T-cell response is essential in preventing severe disease courses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also revealed that immunocompromised patients had a consistently lower prevalence of anti-SARS-CoV-2 antibodies compared to immuno-competent persons [ 12 ]. Liver transplant recipients showed a lower prevalence of anti-nucleocapsid and anti-spike IgG antibodies one year after SARS-CoV-2 infection [ 13 ]. Kidney transplant patients were able to generate normal (but delayed) serum levels of anti-SARS-CoV-2 IgG upon infection, with serum antibody levels decreasing more rapidly compared with immunocompetent subjects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%